2012
DOI: 10.4172/2157-7064.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Simple Estimation of Uncertainty in the Quantification of Cefazolin by HPLC and Bioassay

Abstract: This work proposes a procedure to estimate the measurement uncertainty for the quantification of cefazolin by high-performance liquid chromatography (HPLC) and microbiological assay (bioassay). HPLC method was performed according to United States Pharmacopeia (USP) and bioassay according to Brazilian Pharmacopeia (FB). The quantification of cefazolin by high-performance liquid chromatography was assess through the calibration curve equation (Y=0.0199 X-0.0323). The HPLC uncertainty was estimated based on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
6
0
7
Order By: Relevance
“…The main sources of uncertainty should be considered in the final uncertainty estimation, including sampling (Wunderli, 2003), matrix effects and interferences, environmental conditions (Leito et al, 2002;Lourenço et al, 2012), uncertainties of mass and volumetric equipment, uncertainties of spectrophoto-metric (Sooväli et al, 2006;Hsu and Chen, 2010) and chromatographic equipment (Anglov et al, 2003;Lourenço, 2012), uncertainties of biological and microbiological responses (Niemi and Miemelã, 2001;Lourenço, 2012), purity of reagents and chemical reference substances (Weitzel, 2012), method validation (Brüggemann and Wennrich, 2002) and random variability (Chui et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main sources of uncertainty should be considered in the final uncertainty estimation, including sampling (Wunderli, 2003), matrix effects and interferences, environmental conditions (Leito et al, 2002;Lourenço et al, 2012), uncertainties of mass and volumetric equipment, uncertainties of spectrophoto-metric (Sooväli et al, 2006;Hsu and Chen, 2010) and chromatographic equipment (Anglov et al, 2003;Lourenço, 2012), uncertainties of biological and microbiological responses (Niemi and Miemelã, 2001;Lourenço, 2012), purity of reagents and chemical reference substances (Weitzel, 2012), method validation (Brüggemann and Wennrich, 2002) and random variability (Chui et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several works regarding the measurement uncertainty from high performance liquid chromatograph methods (Okamoto et al, 2013;Ghisleni et al, 2014b), UV spectrophotometric methods (Saviano and Lourenço, 2013) and microbiological assays (Lourenço, 2012;Ghisleni et al, 2014a) have been reported in literature. However, as found in literature, there is no work describing the identification and quantification of main sources of measurement uncertainty from capillary electrophoresis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Na técnica cromatográfica, quanto menor o tamanho da partícula interna que reveste a coluna cromatográfica, maior o número de pratos teóricos, ou seja, é mais eficiente a separação das substâncias que eluem próximas. (CIOLA, 1998, SKOOG et al, 2002 (ANGLOV et al, 2003, LEITO et al, 2002, LOURENÇO et al, 2005, LOURENÇO 2012, LOURENÇO et al, 2004, LOURENÇO et al, 2007, NIEMI et al, 2001, SOOVÄLI et al, 2006, LOURENÇO 2013, OKAMOTO et al, 2013, HSU 2010.…”
Section: Materiais E Métodosunclassified
“…As variáveis comuns, que podem influenciar o espectro de absorção de uma substância, incluem a natureza do solvente, o pH da solução, a temperatura, as concentrações de eletrólitos e a presença de substâncias interferentes (SKOOG et al, 2002 (CHAMBERS 2006, BUTLER et al, 2011. Os métodos reportados na literatura para a determinação de linezolida incluem espectrofotometria em UV, HPLC usando detecção em UV e fluorescência, eletroforese capilar, TLC seguida de análise densiométrica e ensaios microbiológicos (LOPES et al, 2010, BORNER et al, 2001, MOHAPATRA et al, 2011, LOPES et al, 2009 (ANGLOV et al, 2003, LEITO et al, 2002, LOURENÇO et al, 2005, LOURENÇO 2012, LOURENÇO et al, 2004, LOURENÇO et al, 2007, NIEMI et al, 2001, SOOVÄLI et al, 2006, LOURENÇO 2013, OKAMOTO et al, 2013, HSU 2010.…”
Section: Introductionunclassified
“…EURACHEM/CITAC, 2012). A incerteza de medição de um resultado pode surgir de muitas fontes, incluindo fatores como amostragem, efeitos da matriz e interferentes, condições ambientais, incerteza proveniente de balanças e equipamentos volumétricos, incerteza proveniente de equipamentos espectrofotométricos e cromatográficos, incertezas provenientes da resposta biológica e microbiológica, pureza de reagentes e substâncias químicas de referência, validação de métodos e erros aleatórios (NIEMI e NIEMELÃ, 2001;BRÜGGEMANN e WENNRICH, 2002;CHUI et al, 2002;LEITO et al, 2002;ANGLOV et al, 2003;WUNDERLI, 2003;LOURENÇO et al, 2004, LOURENÇO et al, 2005, SOOVÄLI et al, 2006LOURENÇO et al, 2007, HSU e CHEN, 2010LOURENÇO, 2012;LOURENÇO et al, 2012, WEITZEL, 2012LOURENÇO, 2013;SAVIANO e LOURENÇO, 2013;GHISLENI et al, 2014; OSTRONOFF e LOURENÇO, 2015).…”
Section: Introductionunclassified